2018
DOI: 10.18267/j.cebr.192
|View full text |Cite
|
Sign up to set email alerts
|

"Be or Not To Be": A Dilemma of Business Policy Support on a Regional Level

Abstract: Regional authorities implement national priorities in business policy according to the current local requirements in their regional development strategy. Unfortunately, their effort to support entrepreneurial spirit and innovations is not as effective as it could be; its tools and institutions are not as well used as they intended. The question arises: where does the problem lie, is it in the means of communication or in the entrepreneurial requirements at the regional level? The main goal of this paper is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Consequently, the EU has newly set a legal duty for large public-interest entities with more than 500 employees to include, in the management report, a non-financial statement linked to CSR [46], see Directive 2013/34/EU, Directive (EU) 2017/1132 and Regulation 2015/884 as updated [15]. The EU motto "united in diversity" neatly fits in with the perception of CSR as a dialogue and interaction between businesses, corporations, and their stakeholders [47] including customers [43] and is reflected by EU policies [48,49], which, so far, lead to only one legal duty regarding CSR for only some subjects-to report about it. Thusly, so far, it is up to the discretion of the businesses how much they will engage with CSR and its six categories, how they use it as competition leverage [44], and inform about it [10].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Consequently, the EU has newly set a legal duty for large public-interest entities with more than 500 employees to include, in the management report, a non-financial statement linked to CSR [46], see Directive 2013/34/EU, Directive (EU) 2017/1132 and Regulation 2015/884 as updated [15]. The EU motto "united in diversity" neatly fits in with the perception of CSR as a dialogue and interaction between businesses, corporations, and their stakeholders [47] including customers [43] and is reflected by EU policies [48,49], which, so far, lead to only one legal duty regarding CSR for only some subjects-to report about it. Thusly, so far, it is up to the discretion of the businesses how much they will engage with CSR and its six categories, how they use it as competition leverage [44], and inform about it [10].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Baštová et al [65] and Dvouletý and Mareš [66] further demonstrated that the highest density of registered businesses (self-employed individuals and business companies) can be found in the capital Prague, which is expected as the capital is the economic and political centre of the country. Other regional scholars [67][68][69][70][71][72] have highlighted the differences between engagement in entrepreneurship and self-employment across the Czech regions, and they further point out that the activity is most densely concentrated around larger towns and cities. It is also well known that the Czech business activity consists mainly of self-employed individuals [73,74].…”
Section: Entrepreneurial Activity In the Czech Republicmentioning
confidence: 99%
“…A problem that is often debated nowadays is that of CG and CSR influences on competitiveness, productivity and financial and non-financial performance, which prompted us to investigate the implications of Directive 2013/ 34 The implementation of the Directive 2013/34/EU in Romania was achieved by Order no. 1938/2016 from 17 August 2016 on the modification and completion of some accounting regulations [2], which requested, as based on the economic-financial data from 2017, reported in 2018, the Administrators' Reports for public-interest entities that, on the date on the balance sheet, they had an average number of over 500 employees and included a non-financial statement containing at least information on environmental, social and personnel issues, respecting human rights, combating corruption and giving bribes.…”
Section: Introductionmentioning
confidence: 99%
“…Second, most of the studies were conducted in economically developed European countries [29][30][31]. In other emerging or developing countries, many organizational, cultural or legislative factors may influence and may have different perspectives and expectations regarding social and environmental protection issues [32][33][34][35][36][37][38]. In the approach taken, the focus is on Romania, which has experienced the biggest economic dynamics in Europe in recent years, a country that is trying to find its way in the complex process of European integration.…”
Section: Introductionmentioning
confidence: 99%